Efficacy of anti-inflammatory drug ulinastatin in coronavirus disease 2019: A case report - Chatterjee, Rupa; Purayil, ShahafazIbi Meethal Puthiya; Ramakrishnan, Raneesh Kumar; Sankaran, Rajesh; Sasikumar, Changam Sheela (Indian Journal of Case Reports, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory coronavirus 2, can affect the respiratory system as well as other systems of the body. It has now become a pandemic and poses a global health emergency. We report the case of a COVID-19-positive 50-year-old male patient with multiple, ground-glass opacities in bilateral lungs. The disease did not respond well to tocilizumab administration and the condition of the patient gradually worsened. We administered ulinastatin along with high doses of steroids. We observed that the overall performance of a combination of ulinastatin and high-dose steroids proved to be effective and routine use of ulinastatin is a potent method of treatment in COVID-19 patients developing acute respiratory distress syndrome, which may save other patients with a similar background.